2017
DOI: 10.1007/s11657-017-0397-1
|View full text |Cite|
|
Sign up to set email alerts
|

Psychometric performance of the Romanian version of the SarQoL®, a health-related quality of life questionnaire for sarcopenia

Abstract: Our results indicate that the Romanian version of the SarQoL questionnaire, qualified in terms of psychometric properties, could be a useful tool to assess the sarcopenia-related QoL among frail Romanian individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
6
15
0
2
Order By: Relevance
“…These 6 studies found that the questionnaire can discriminate between sarcopenic and non-sarcopenic participants, with the former having significantly lower scores for the 7 domains and the overall score, and that the questionnaire possesses good internal consistency (Cronbach's alpha of 0.87, 0.88, 0.95, 0.92, 0.88 and 0.96). These studies also confirmed the construct validity of the SarQoL questionnaire with the help of hypotheses on correlations between the questionnaire and the SF-36 and EQ-5D, and demonstrated that the SarQoL questionnaire has an excellent test-retest reliability (intraclass correlation coefficient/ICC = 0.91, 0.95, 0.99, 0.98 and 0.96) [9][10][11][12][13][14]. Lastly, floor and ceiling effects were absent from all 6 published validation studies [9][10][11][12][13][14].…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…These 6 studies found that the questionnaire can discriminate between sarcopenic and non-sarcopenic participants, with the former having significantly lower scores for the 7 domains and the overall score, and that the questionnaire possesses good internal consistency (Cronbach's alpha of 0.87, 0.88, 0.95, 0.92, 0.88 and 0.96). These studies also confirmed the construct validity of the SarQoL questionnaire with the help of hypotheses on correlations between the questionnaire and the SF-36 and EQ-5D, and demonstrated that the SarQoL questionnaire has an excellent test-retest reliability (intraclass correlation coefficient/ICC = 0.91, 0.95, 0.99, 0.98 and 0.96) [9][10][11][12][13][14]. Lastly, floor and ceiling effects were absent from all 6 published validation studies [9][10][11][12][13][14].…”
Section: Introductionsupporting
confidence: 55%
“…These studies also confirmed the construct validity of the SarQoL questionnaire with the help of hypotheses on correlations between the questionnaire and the SF-36 and EQ-5D, and demonstrated that the SarQoL questionnaire has an excellent test-retest reliability (intraclass correlation coefficient/ICC = 0.91, 0.95, 0.99, 0.98 and 0.96) [9][10][11][12][13][14]. Lastly, floor and ceiling effects were absent from all 6 published validation studies [9][10][11][12][13][14]. These results provide convincing evidence for the validity and reliability of the SarQoL questionnaire for the evaluation of quality of life in sarcopenic, community-dwelling older people.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“… 5 , 7 , 8 ) The alpha value in our study was lower than those in the Greek, Lithuanian, Romanian, and Polish validation studies (0.960, 0.950, 0.946, and 0.920, respectively) suggesting that some questions in the SarQoL may be redundant. 9 , 10 , 13 , 25 ) However, although the internal consistency of the Ukrainian was excellent, this does not mean that cross-cultural effects are, therefore, excluded. Although we paid particular attention to cross-cultural equivalence, Ukrainian participants may have responded differently to certain questions.…”
Section: Discussionmentioning
confidence: 97%
“…In accordance with the global need for a sarcopenia specific QoL assessment tool, it has been translated into 28 languages under the leadership of the creators [Charlotte Beaudart (CO), Olivier Bruyere (OB)]. So far, its cross-cultural adaptation and psychometric validation has been performed in seven (English, Romanian, Dutch, Polish, Spanish, Greek, and Hungarian) languages [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%